2014
DOI: 10.1007/s10557-014-6555-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) Modulates Angiotensin II-Induced Vasoconstriction in Human Mammary Artery

Abstract: ANG-(1-7) significantly attenuates ANGII-induced vasoconstriction and, although the Mas receptor is expressed in HMA, this effect seems to be independent of its activation. Additionally, AT2 receptor and endothelium are not involved in this mechanism, which suggests a direct effect on smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The same authors (560) demonstrated that the effect of ANG-(1-7) infusion on renal blood flow was also reduced in stenotic kidneys. Mendonça et al (359) have recently demonstrated that ANG-(1-7) significantly attenuates ANG IIinduced vasoconstriction in human mammary arteries from patients submitted to coronary revascularization, probably through direct effects on smooth muscle cells, since this action was not abolished by A-779, PD123177, or endothelium removal.…”
Section: As For Antithrombotic Effects Experiments Performed Inmentioning
confidence: 99%
“…The same authors (560) demonstrated that the effect of ANG-(1-7) infusion on renal blood flow was also reduced in stenotic kidneys. Mendonça et al (359) have recently demonstrated that ANG-(1-7) significantly attenuates ANG IIinduced vasoconstriction in human mammary arteries from patients submitted to coronary revascularization, probably through direct effects on smooth muscle cells, since this action was not abolished by A-779, PD123177, or endothelium removal.…”
Section: As For Antithrombotic Effects Experiments Performed Inmentioning
confidence: 99%
“…Secondly, SW increased the blood pressure in the WKY rats and exacerbated the blood pressure in the SHR. This is mainly attributed to the increase in the levels of ANG-II in the serum caused by metabolic disorders, as well as increased expression of AGTR and decreased expression of eNOS in the carotid artery, ultimately resulting in increased blood pressure [60][61][62] . In addition, metabolic disorders trigger an elevation in the levels of IL-6, resulting in an increase in the inflammatory response of the blood vessel [63,64] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the decrease in compliance was primarily associated with the increase in the content of collagen fiber in the vessel wall [67][68][69] , and the imbalance in the ratio of eNOS to AGTR expression in the vessel wall. [60][61][62] However, with respect to the blood flow velocity, the effects of SW on the carotid arteries of the two types of rats were not identical. In the WKY rats, SW reduced the diameter of the carotid artery and increased the blood flow velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, pre‐incubation with the specific MAS1 antagonist A‐779 did not abolish this effect of AngII. Furthermore, the Ang(1–7) effect observed in HMA was not altered by the AT 2 receptor antagonist PD123177, indicating a pharmacologically distinct receptor in HMA (Mendonca et al, ).…”
Section: Confusing Evidencementioning
confidence: 99%
“…There is evidence in the literature for additional receptors mediating the effects of Ang(1–7) (Figure ). For example, the AT 2 receptor was shown to bind Ang(1–7) (De Souza et al, ; Walters et al, ) and Ang(1–7) signals through AT 2 receptors in some studies (Jones et al, ; Sipahi et al, ; Ohshima et al, ), although this is not replicated in all settings (Lautner et al, ; Mendonca et al, ; Tetzner et al, ). De‐orphanization efforts on the MAS1‐related GPCR (MRGPR) family have uncovered potential new receptors for consideration in the ACE2/Ang(1–7) pathway (Gembardt et al, ; Solinski et al, ).…”
Section: Introductionmentioning
confidence: 99%